In Vitro BACE1 Inhibitory Activity of Geraniin and Corilagin from Geranium thunbergii - Youn, Kumju; Jun, Mira (Planta Medica, 2013)
Generation of amyloid β peptide through the proteolytic process of amyloid precursor protein by β-secretase and γ-secretase is a main casual factor of Alzheimerʼs disease, since amyloid β peptide is a major and crucial component of senile plaques in Alzheimerʼs disease brains. In the process of searching for β-secretase inhibitors from natural resources, the EtOAc soluble fraction of Geranium thunbergii exhibited significant β-secretase inhibitory activity. Two compounds, geraniin and corilagin, isolated from the most active EtOAc fraction of G. thunbergii, exhibited predominant inhibition against β-secretase with IC50 values of 4.0 × 10−6 M and 3.4 × 10−5 M, respectively. Dixon plot of geraniin and corilagin demonstrated that the β-secretase inhibition was noncompetitive with the substrate, thus clearly suggesting that these compounds might bind either to the β-secretase subsites or to another regulatory domain with Ki values of 2.8 × 10−6 M and 7.9 × 10−5 M, respectively. Both compounds exhibited no significant inhibition against α-secretase and other serine proteases including trypsin and chymotrypsin, showing that they were relatively specific and selective inhibitors of β-secretase. These novel findings suggest that geraniin and corilagin from G. thunbergii may be effective therapeutic agents for further drug development in Alzheimerʼs disease.
Keywords: Alzheimerʼs disease; amyloid β peptide; β-secretase; Geranium thunbergii; Geraniaceae